The Prevalence of Human Papilloma Virus in Squamous Cell Carcinoma of Oral Tongue - Ashraf, Mohamad Javad; Hosseini, Shahla; Monabati, Ahmad; Valibeigi, Behnaz; Khademi, Bijan; Abedi, Elham; Azarpira, Negar (Iranian journal of pathology, 2017)
Oral tongue Squamous Cell carcinoma (SCC) commonly involves males between the sixth to eighth decades of life. Major risk factors are tobacco usage and alcohol consumption. The increasing number of patients developing oral tongue cancer without these well-known risk factors suggests that a viral infection, such as Human Papillomavirus (HPV), may be responsible for this increase, by acting as an oncogenic agent. This study investigated the prevalence of HPV infection and its clinicopathologic significance in oral tongue SCCs. Tissue blocks from a total of 50 cases (patients with oral tongue SCC) and 50 controls (palatine tonsillar tissues with benign diagnosis) were selected. DNA was extracted from tumoral and non-tumoral tissue blocks. Detection of common HPV DNA by nested Polymerase Chain Reaction (PCR), and high-risk genotypes, HPV 16 and HPV 18, by conventional PCR, was achieved and the results correlated with clinicopathological parameters. Of the 50 patients (18 males and 32 females with a mean age of 57.36±12.18 years, and age range of 27 to 86 years), 7 (14%) had HPV positive results. None of the control group subjects had HPV DNA positive results (P-value of 0.012). The HPV genotype 16/18 was not detected in positive cases. No statistically significant association was found between HPV status and gender, age, tumor grade, tumor stage or lymph node involvement. Although there was a significantly higher prevalence of HPV in oral tongue SCC, its association with carcinogenesis in this area requires further studies.